Ultrasonic monitoring of corroding bolted joints. (August 2019) - Shah, Jay Kumar; Braga, Henrique Bastos Fabrino; Mukherjee, Abhijit; Uy, Brian
Abstract: Ensuring adequate tightening is imperative for securing bolted connections in steel structures. Moreover, bolted joints are affected by corrosion. This paper describes a method of non-destructively assessing the condition of bolted joints. An ultrasonic pulse transmission technique for inspection of bolted joints has been described. Steel plates have been bolted by applying different levels of torque. Transmission of ultrasonic pulse through the joint with varying tightening is studied. A set of plated joints have been subjected to tensile testing to characterise the joints. The other set of joints have been subjected to accelerated corrosion and the ultrasonic measurement has been conducted regularly. After the exposure period, the joints have been subjected to tensile tests to compare with the control specimens. It is observed that the ultrasonic pulse transmission can be correlated with the initial tightening of the bolt. The effect of corrosion was also discerned through ultrasonic measurement. It is observed that the tensile behaviour of the joints due to corrosion is affected significantly by the initial tightening. The proposed method can be applied for non-invasive inspection of fresh and corroded steel structures. Highlights: Extent of corrosion damage in the bolted joint depends on the bolt torque. Ultrasonics based technique can be used monitor the condition of bolted joints. Corrosion's effects on the load capacity of the joints depend on the bolt tightening